Qualities of movement: travel and environment in modern epic literature - Wood, Melanie (2003)
Epic literature has often been interpreted as a static genre, conforming to conventional structural and thematic characteristics. This study argues that epic is a genre of movement and transition, in terms of its literary style, and its humanist representation of journeys and geography.